Answer to Question #22492 in Trigonometry for Kristen Woods
Solve the given equations.
11a. x^(2/3)+6x^(1/3)=7
11b. (y+3)^2-8(y+3)+12=0
1
2013-01-21T11:16:14-0500
11a. x^(2/3)+6x^(1/3)=7let t=x^(1/3)
t^2+6t-7=0
From Vieta's theorem
t1=1, t2=-7
x1=1^3=1, x2=(-7)^3=-343
x1=1 x2=-343
11b.(y+3)^2-8(y+3)+12=0
let y+3=t
t^2-8t+12=0
t^2-8t+16=4
(t-4)^2=4
t-4=+-2
t1=6, t2=2
then y1=3, y2=-1
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment